2014
DOI: 10.2306/scienceasia1513-1874.2014.40.193
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of flavonoids from leaves of Jatropha curcas

Abstract: The objective of this study was to characterize the antioxidant properties of ethanol extracted from leaves of Jatropha curcas and to determinate the compounds. The IC 50 values of DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2 -azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) diammonium salt) were found to be 7.47 and 6.6 µg/ml, respectively, for the extracts. The reducing power of the extracts increased from 0.09 to 0.16, respectively, for 1-32 µg/ml of standard reagent. The assignment of the flavone c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…The characteristic UV spectra, their retention time and co-elution with authentication standard let us to identify compounds as vicenin-2 ( 1 ); stellarin-2 ( 2 ); vitexin ( 3 ); isovitexin ( 4 ); isorhoifolin ( 5 ); and rhoifolin ( 6 ). Several of these compounds have already been reported in other leaves of Jatropha curcas L. (although grown in conditions different from the one tested in our experiment) and Jatropha genus suggesting a common pattern of flavonoids that are conserved in the species and may represent an indication of the endogenous adaptation of the plant to Calabrian marginal areas [17,52,53,54,55,56,57,58]. …”
Section: Resultssupporting
confidence: 68%
“…The characteristic UV spectra, their retention time and co-elution with authentication standard let us to identify compounds as vicenin-2 ( 1 ); stellarin-2 ( 2 ); vitexin ( 3 ); isovitexin ( 4 ); isorhoifolin ( 5 ); and rhoifolin ( 6 ). Several of these compounds have already been reported in other leaves of Jatropha curcas L. (although grown in conditions different from the one tested in our experiment) and Jatropha genus suggesting a common pattern of flavonoids that are conserved in the species and may represent an indication of the endogenous adaptation of the plant to Calabrian marginal areas [17,52,53,54,55,56,57,58]. …”
Section: Resultssupporting
confidence: 68%
“…Based on the molecular ion, MS-MS fragmentation profile and the predictive structures obtained by CFM-ID platform, it is suggested the tentative identification of vitexin m/z of 433 [M+H] + , vicenin-2 m/z of 595 [M+H] + , and vitexin 4 -O-glucoside-2 -O-rhamnoside m/z of 741 [M+H] + in leaves and callus from both varieties. These results are similar to obtained by Huang et al (2014) who identified vitexin m/z of 433 [M+H] + in J. curcas leaves. This flavonoid was also identified by ESI-MS in Parkinsonea aculeata m/z of 431 [M-H] − (Hassan, Abdelaziz & Al Yousef, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Flavonoids are recognized as polyphenols. Several of them have been identified in Jatropha genus, such as apigenin glycosides, vitexin, and isovitexin which have been considered as chemiotaxonomic compounds from the genus (Abdelgadir &Van Staden, 2013;Huang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The Indian spice Cinnamomum tamala leaf is known for its antioxidant [ 34 ], as well as antibacterial properties [ 35 ], and similar properties are found in the case of Jatropha curcas latex as well [ 36 , 37 ]. Several MNPs have been synthesized with natural product extracts like neem [ 38 ], bhringraj [ 39 ], curcumin [ 40 ], etc.…”
Section: Introductionmentioning
confidence: 99%